Determinan Kinerja Karyawan Kementerian Keuangan dengan Budaya Kaizen sebagai Moderator - Yunizar; Hardiansyah, Achmad; Muizu, Wa Ode Zusnita (Universitas Negeri Surabaya, 2024)
This study aims to determine the effect of leadership empowerment and work engagement moderated by kaizen culture on employee performance within the Secretariat General of the Ministry of Finance of Indonesia. This research is a quantitative study with an explanatory survey approach. Respondents in this study amounted to 180 people from a total population of 221 people determined using the Isaac and Michael method and cluster random sampling technique because respondents were spread across several fields. The data management technique in this study uses path analysis. Work engagement moderated by kaizen culture has a significant positive impact both partially and simultaneously on the performance of employees of the Secretariat General of the Ministry of Finance. In addition, leadership empowerment moderated by kaizen culture has no significant impact on employee performance. The relationship between leadership empowerment and work engagement with employee performance among Ministry of Finance employees is direct and positive, meaning that an increase in leadership empowerment and work engagement will improve employee performance. In addition, an increase in work engagement moderated by kaizen culture will improve the performance of Ministry of Finance employees